Predictors of Outcome Post Cardiac Arrest. (April 2018) - Bigham, S.; Bigham, C.; Martin, D.
Early predictors of prognosis in comatose patients post cardiac arrest help inform decisions surrounding continuation or withdrawal of treatment and provide a framework on which to better inform relatives of the likely outcome. Markers defined prior to the widespread use of therapeutic hypothermia post arrest may no longer be reliable and an up-to-date analysis of the literature is presented.